Instruction & Examination System in Higher Education in India in the Context of Global Competition - Hariharan, R.; Balasubramanian, N. (Journal of Engineering Education Transformations, 2006)
Higher education has special value in the emerging knowledge Society. What are the long-term implications of the trend toward privatization and commercialization of higher education? The thrust of globalization is expected to push Higher education to face far-reaching challenges. Today it is increasingly realized that knowledge is universal and its creation and dissemination cannot be confined within national boundaries. The globalization of economy has led to internationalization of higher education, not merely for economic benefits, but also for increased social interaction and promotion of international understanding. While a lot of debate has gone on the support of higher education by the Government, the fact remains that in real terms the support has dwindled continually. The demand for higher technical education has progressively and substantially increased resulting in the establishment of a large number of self-financed technical institutions Fundamental to education is the need to evaluate student learning and the effectiveness of teaching methods and the programs offered. It is a well known fact that any change in methods of teaching, textbook and reference book writing, study habits of students, etc. can be brought by way of changing the examination system. Reforms in the examination system by adopting Continuous Internal Evaluation and well defined Academic Auditing are the need of the hour. This paper attempts to highlight the status of higher education in the context of globalization and suggests a few examination reforms for the betterment of the system.